The Beautiful and the Dammed: Defining Multi-Stressor Disturbance Regimes in an Atlantic River Floodplain Wetland - Rideout, Natalie K.; Compson, Zacchaeus G.; Monk, Wendy A.; Bruce, Meghann R.; Baird, Donald J. (Frontiers in Ecology and Evolution, 2021)
Natural hydrological fluctuations within river floodplains generate habitat diversity through variable connections between habitat patches and the main river channel. Human modification of floodplains can alter the magnitude and frequency of large floods and associated sediment movement by interrupting these floodplain connections. The lower Wolastoq | Saint John River and its associated floodplain wetlands are experiencing anthropogenic disturbances arising from climate change, increased urbanization in the watershed, changing upstream agricultural landscape practices, and, most notably, major road and dam construction. By comparing digitized aerial images, we identified key periods of change in wetland extent throughout an ecologically significant component of the floodplain, the Grand Lake Meadows and Portobello Creek wetland complex, with significant erosion evident in coves and backwater areas across the landscape following dam construction and significant accretion around the Jemseg River following highway construction. Connectivity and hydrological regime also influenced other habitat components, namely nutrients and metals retention, as well as the composition of the local macrophyte community. These findings address two key aspects of floodplain management: [1] understanding how hydrological alteration has historically influenced floodplain wetlands can inform us of how the ecosystem may respond under changing future conditions, such as climate change, and [2] the mechanisms by which habitat diversity and disturbance regimes filter biological communities, with the potential for patches to host a rich biodiversity continuously supporting critical ecosystem functions.